Original paperKINEMATICS THAT DIFFERENTIATE THE BEACH FLAGS START BETWEEN ELITE AND NON-ELITE SPRINTERS - Lockie, R.G.; Vickery, W.M. (Biology of Sport, 2013)
This study differentiated the kinematics of the beach flags sprint start between five elite (three males, two females; age = 21.2 ± 2.6 years; height = 1.71 ± 0.04 m; mass = 66.2 ± 5.9 kg) and five non-elite (three males, two females; age = 20.4 ± 1.7 years; height = 1.69 ± 0.08 meters [m]; mass = 61.6 ± 5.7 kilograms) sprinters. A high-speed camera filmed the start. Timing gates recorded the 0-2, 0-5, and 0-20 m intervals. Data included body position during the start and at take-off; start time; first step length; and sprint times. A Mann-Whitney U-test determined significant (p < 0.05) between-group differences; effect sizes (ES) were also calculated. Elite sprinters had a greater take-off trajectory angle (p = 0.01; ES = 2.57), and were faster over the 0-2 (p = 0.02; ES = 1.77), 0-5 (p = 0.05; ES = 1.20), and 0-20 m (p = 0.02; ES = 1.83) intervals. Large effects were found for: greater take-off swing leg hip flexion (ES = 1.13) and trunk lean (ES = 1.37); longer duration start time (ES = 1.33); and longer first step length (ES = 1.23) in elite sprinters. A longer start time assists with force generation, which in conjunction with increased hip flexion, could translate to a longer first step. Increased trunk lean shifts the take-off trajectory angle towards the horizontal. A greater trajectory angle at start take-off, which could be advantageous for force production during sprint performance, is likely necessary for beach flags.